Fluoride Varnish Effect on Dental Erosion Immersed with Carbonated Beverages - Sunniyah Harum Adiba, -; Ruslan Effendy, -; Nanik Zubaidah, - (Ektodermal Displazi Grubu, 2018)
Dental erosion is still occurring worldwide due to exposure of the enamel to non-bacterial acids. Dental erosion may cause mineral loss occurs from the surface of the tooth (demineralization). Demineralization of dental enamel will occur when oral environmental pH reaches the critical threshold 5.5. Carbonic acid drinks is one of acid source which widely consumed. Fluoride has an important role in remineralization process. Topical fluoride is one of treatment choices to strengthen enamel and dentin. This material contains 5% or 22.600 ppm of sodium fluoride. To analyze the effectiveness of fluoride varnish to prevent dental erosion caused by carbonic acid drinks. 21 bovine teeth divided into 3 groups. Group I (control) which submerged on artificial saliva and aquadest. Group II (Treatment I) with submerged in erosive cycling. Group III (Treatment II) treated with fluoride varnish application and submerged in erosive cycling. The sections of the teeth were examined under Scanning Electron Microscop-Energy Dispersive X-Ray (SEM-EDX). The data were analyzed using the Kruskal-Wallis Test, Tukey HSD, and Pearson Correlation test. Group I showed the average of erosion depth is 12,0445µm and fluoride composition is 2,4314%, Group II showed the biggest average of erosion depth 100,15 µm and fluoride composition 1,6043%, and Group III showed the average erosion depth is 26,5886 µm and fluoride composition is 4,3471%. There is a correlation between the depth of dental erosion and fluoride content. The depth of dental erosion caused by carbonic acid decreased after fluoride varnish application.